The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1136/tsaco-2022-000904
|View full text |Cite
|
Sign up to set email alerts
|

A multi-institutional prospective observational study to evaluate fascia iliaca compartment block (FICB) for preventing delirium in adults with hip fracture

Abstract: ObjectivesUntil recently, systemic opioids have been standard care for acute pain management of geriatric hip fracture; however, opioids increase risk for delirium. Fascia Iliaca compartment blocks (FICB) may be favored to systemic analgesia for reducing delirium, but this has not been well demonstrated. We evaluated the efficacy of adjunctive FICB versus systemic analgesia on delirium incidence, opioid consumption, and pain scores.MethodsThis prospective, observational cohort study was performed in patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Current practice is to prescribe non-opioid medications and to increase opioids (per oral then intravenous) once the patient’s pain is not adequately controlled based on self-reported pain scores. We did not evaluate non-opioid analgesics as part of multimodal pain management in this analysis; when they were examined in the main prospective study, we found no differences in their administration between FICB and no FICB groups 3…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Current practice is to prescribe non-opioid medications and to increase opioids (per oral then intravenous) once the patient’s pain is not adequately controlled based on self-reported pain scores. We did not evaluate non-opioid analgesics as part of multimodal pain management in this analysis; when they were examined in the main prospective study, we found no differences in their administration between FICB and no FICB groups 3…”
Section: Discussionmentioning
confidence: 99%
“…We did not evaluate non-opioid analgesics as part of multimodal pain management in this analysis; when they were examined in the main prospective study, we found no differences in their administration between FICB and no FICB groups. 3 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though the elderly usually suffers a hip fracture after a minor trauma, the consequences are major. For the geriatric patient, who often show multi-morbidity and ger iatr ic sy ndromes (i.e., frai lt y, malnutr ition, polypharmacy, cognitive impairment, and mental disorders), these fractures result in: a) higher mortality rates of 8-10% in the first 30 days and 15-30% within the first year of the hip fracture (Verbeek 2021); b) longer length of stay (LOS); reduced quality of life with 10% of patients never returning to their own residence, but to alternative long-term care as they become dependent of care takers [6] and d) a high incidence of postoperative delirium, ranging from 4 to 53%, which is the most common complication of hip fracture surgery and which is also associated with a higher mortality rate [6][7][8][9][10]. Furthermore, hip fractures are one of the most expensive clinical conditions with huge costs related, estimated at 20 billion US$ spent annually on this injury and about 1% of the annual NHS budget in the UK [11].…”
Section: Hip Fractures-the Most Frequently Occurring Severe Injury In...mentioning
confidence: 99%